Effect of lean six sigma on firm performance: A case of Indian automotive component manufacturing organization. (2021) - Swarnakar, Vikas; Singh, A.R.; Tiwari, Anil Kr
Abstract: The main focus of this article is to assess the effects of Lean Six Sigma (LSS) adaptation on firm performances. The study was conducted on various automotive components manufacturing organizations located in different regions within India. The effects on firm performances were identified by using an integrated approach. However, factor analysis and multiple regression analysis approaches were performed to evaluate the questionnaire survey data. The analysis observed the financial performance was more impacted than others while LSS adaptation in automotive components manufacturing organization. Also, the adaptation of LSS leads these firms to enhance their other performances such as customer, learning, and growth and business process performances.